Fostering creative writing among gifted intermediate pupils - Tiburcio, Perla A. (College of Education, University of the Philippines Diliman, 1968)
Creative writing is a means by which an individual expresses his ideas, feelings and reactions. It is original, productive and is based on an innate desire to express oneself. This paper explored ways of fostering creative writing among gifted intermediate pupils. The study concluded that the teacher plays an important role in the creative process. He is to inspire and encourage creative expression and to provide a learning environment conducive for creative writing. Creative writing needs to be evaluated, but its emphases are on creative content, approval and recognition.